Governance reforms and national benefits : problems and prospects in Marange diamond mining in Zimbabwe - Makombe, Percy Fungayi (Graduate School of Development Policy and Practice, 2016)
Zimbabwe is among the top diamond-producing countries and is believed to hold a quarter of the world's diamond reserves. Yet it is still one of the poorest countries as the economy is slumped and growth has slackened, and it is expected to further weaken. This study tracks the history of diamond mining at Marange diamond fields, describing what has played out since the discovery of huge diamond deposits in 2006.The study considers potential entry points to try and effect reform in diamond mining in the country. It also explores the governance options and their experience, distinguishing between domestic and global mechanisms and exploring the prospects for each. The study interrogates the strength and ability of various stakeholders to affect reform casting light on the politics and power dynamics at play.